Influence of Chlorella Vulgaris Microalgae on the Adsorption of Pb and Zn in Leachates at El Porvenir Open-Air Dump-— “El Tambo” - Zegarra Jara, Mayly Yanira (2024)
The application of Chlorella vulgaris microalgae in the adsorption of heavy metals is an economical and very efficient method. Being negatively charged, the heavy metals have a high affinity with polyvalent metal ions. The adsorption capacity of Zinc (Zn) and Lead (Pb) found in the leachate was studied taking into account the biomass production indices of the microalgae. In order to evaluate its adaptability in the environment, a pilot test was carried out with 2 samples: MP01 consisting of 3 L of leachate + 100 mL of Chlorella vulgaris; MP02 consisting of 3L of leachate + 200 mL of Chlorella vulgaris. The results of the pilot test showed that the leachate concentration was unfavorable for its growth; for this reason, it was decided to carry out a second experimental test with a dilution of 1:3, thus creating the necessary conditions for its growth. M01 made up of 3 L of dilution + 250 mL of Chlorella vulgaris and M02 made up of 3 L of dilution + 500 mL of Chlorella vulgaris. The results indicated that M02 presented better adaptability in the dilution; Regarding the adsorption of Pb, M01 presented an absorption of 72.09% and M02 reached an adsorption of 53.40%. For Zn adsorption, M01 had an adsorption of 88.98% and M02 reached an adsorption of 94.13%. It is concluded that the Chlorella vulgaris microalga can adapt to the leachate in a 1:3 dilution and with an optimal concentration of 500 mL, it is also significantly effective in the adsorption of Zn and Pb.